Optimasi Perbandingan CMC-Na dan HPMC pada Gel Ekstrak Biji Lamtoro (Leucaena leucocephala) Menggunakan Metode Simplex Lattice Design - Kiki Puspitasary (Fakultas Farmasi Universitas Setia Budi, 2026)
Lamtoro is a traditionally cultivated plant, this is due to its therapeutic properties and chemical content and in lamtoro seeds contain flavonoids that function as antioxidants. The use of lamtoro seed extract can provide a protective effect from skin damage due to photoaging and carciogenesis. The effectiveness of the drug will be maximized if given to a preparation such as a gel. The type and concentration of gel used will affect physical properties and physical stability. This study aims to determine the effect of gelling agent concentration on the physical properties and physical requirements of gel preparations. Evaluation of gel preparations includes pH tests, dispersion tests, adhesion and viscosity tests. The results showed that there was an influence of gelling agent concentration on the physical properties and physical requirements of gel preparations, which was reinforced by the results of One-Way ANOVA statistical analysis where a significance value of <0.05 was obtained which can be concluded that there is an influence of gelling agent concentration.